Bacteriological Quality of Bottled Drinking Water and Municipal Tap Water in Northeastern Ethiopia - Keleb, Awoke; Ademas, Ayechew; Sisay, Tadesse; Lingerew, Mistir; Adane, Metadel (Frontiers in Environmental Science, 2022)
Objective: Water-borne diseases cause high morbidity and mortality in developing countries, like Ethiopia. Preservation of the bacteriological quality of drinking water has been used as a crucial method of preventing waterborne disease. This study aimed to determine the bacteriological quality of bottled drinking water and municipal tap water in Northeastern Ethiopia for proper planning, monitoring, and intervention purpose. Methods: A laboratory-based cross-sectional study was conducted on 248 municipal tap water samples from point of collection (MTPOC), 248 water samples from a household water storage container (HHSC) and 38 bottled water samples before packaging from manufacturing facilities (BPMF), and 38 bottle water samples from point of sale (POS) in Dessie city between March and May 2021. Water samples were collected by trained data collectors using a standard sampling protocol. Data were entered into Microsoft Excel and exported to SPSS version 25.0 for data cleaning and analysis. The commonest microbiological parameters, total coliforms (TC) and Escherichia coli (E. coli), were tested using the standard procedure. One way ANOVA was used to compare the mean log concentration of E. coli and TC between sampling points and Tukey post hoc test was also computed to identify statistical significant deference among sample types. The 95% confidence interval [CI] and p<0.05 were taken as statistically significant Results: About 15.8% and 36.8% of the samples from BPMF and 26.3% and 55.3% of samples from POS were positive for E. coli and TC respectively while 47.2% and 65.7% of water sample from MTPOC and 48.8% and 98.8% of samples from HHSC were positive for E. coli and TC respectively. The mean log concentration of E. coli from sample of MTPOC was significantly higher than BPMF. Similarly, water samples from HHSC had significantly higher E. coli and TC concentrations than BPMF and POS. Water samples from HHSC had also significantly higher prevalence of log concentrations of TC than MTPOC. Conclusion: Most values were beyond maximum tolerable limits recommended by World Health Organization (WHO). Thus, good water handling practices and water quality monitoring are essential to prevent bacteriological contamination.